Case Report: Pheochromocytoma and Synchronous Neuroblastoma in a Family With Hereditary Pheochromocytoma Associated With a MAX Deleterious Variant - Duarte, Diana Borges; Ferreira, Lia; Santos, Ana P.; Costa, Cláudia; Lima, Jorge; Santos, Catarina; Afonso, Mariana; Teixeira, Manuel R.; Carvalho, Rui; Cardoso, Maria Helena (Frontiers in Endocrinology, 2021)
IIntroduction: Pheochromocytomas are rare catecholamine-producing neuroendocrine tumours arising from chromaffin cells of the adrenal medulla or extra-adrenal sympathetic paraganglia. Recent studies have indicated that up to 40% of pheochromocytomas could be attributable to an inherited germline variant in an increasing list of susceptibility genes. Germline variants of the MYC-associated factor (MAX) gene have been associated with familial pheochromocytomas and paragangliomas with an autosomal dominant pattern of inheritance, a median age at onset of 33 years and an overall frequency estimated at 1.9%. We describe a deleterious MAX variant associated with hereditary pheochromocytoma in a family with four affected individuals. Case presentation: The first patient presented with bilateral pheochromocytoma in 1995; genetic testing was proposed to his oldest son, when he was diagnosed with a bilateral malignant pheochromocytoma with a synchronous neuroblastoma. Upon the identification of the MAX variant c.97C>T, p.(Arg33Ter), in the latter individual, his two siblings and their father were tested and the same variant was identified in all of them. Both siblings were subsequently diagnosed with pheochromocytoma (one of them bilateral) and choose to remain on active surveillance before they were submitted to adrenalectomy. All the tumours secreted predominantly norepinephrine, accordingly to the typical biochemical phenotype ascribed to variants in the MAX gene. Conclusion: This case series is, to our knowledge, the one with the largest number of individuals with hereditary pheochromocytoma with a deleterious MAX variant in the same family. It is also the first case with a synchronous pheochromocytoma and neuroblastoma in carriers of a MAX deleterious variant. This report draws attention to some ill-defined features of pheochromocytoma and other malignancies associated with a MAX variant and highlights the importance of understanding the genotype-phenotype correlation in hereditary pheochromocytoma and the impact of oriented genetic testing to detect, survey and treat patients and kindreds at risk